A goblet-like non-linear electromagnetic generator for planar multi-directional vibration energy harvesting. (15th May 2020) - Gu, Yuhan; Liu, Weiqun; Zhao, Caiyou; Wang, Ping
Highlights: A novel method of designing wideband planar generators is proposed by extending the bi-stable structure to 3-D space. Equivalence for vibrations form any direction in plane due to the centrosymmetric structure. Improved performance for low-frequency vibrations by engaging the mass in circular motions. The comparatively light and compact structure is suitable for human body energy harvester. Abstract: A novel electromagnetic energy harvester for in-plane multi-directional vibrations is developed by letting a magnetic ball move on a two-dimensional surface which is generated from the rotation of a one-dimensional bi-stable potential curve. A goblet-like structure is designed to keep the ball on the nonlinear potential surface. Due to the special symmetric configuration, in-plane excitations from any direction can equivalently force the motion of the magnetic ball and thus produce electricity in the coils on the outer surface of the structure. Meanwhile, the good features of nonlinearities on bandwidth extension are preserved. Continual circular motions were observed for a wide frequency range. The operation bandwidth could reach a high value of 8 Hz and simultaneously the maximum power of 7.649mW was captured in experiments under a harmonic excitation of 1 g, corresponding to a normalized power density of 72.5 µW cm −3 g −2 . In particular, the proposed harvester showed good performance for low frequency vibrations and is especially suitable for human body energy harvesting. With the harvester attached to the ankle, 1.4mW was obtained when walking at 5 km h −1 . Notably, the method can be applied to other one-dimensional potential portraits for constructing the corresponding two-dimensional potential surface.